2020
DOI: 10.1063/1.5132751
|View full text |Cite
|
Sign up to set email alerts
|

Filter function of graphene oxide: Trapping perfluorinated molecules

Abstract: We need clean drinking water, but current water purification methods are not always sufficient. This study examines the binding and binding mechanisms when graphene oxide is used as a filter material for removing perfluorinated substances and trihalomethanes. We use density functional theory calculations to examine the binding of the harmful molecules on graphene oxide. Our results indicate that the binding energies between graphene oxide and the investigated molecules are in the range of 370–1450 meV per mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Barker et al reported binding energies between GO flakes and perfluorinated molecules calculated using density functional theory (DFT) and suggested Van der Waals interactions dominate adsorption. 41 Li et al used first-principles computations of iron on GO flakes to calculate binding strengths as well. 42 Surface complexation modelling has shown some metals adsorb by interacting with carboxyl groups located on the GO flakes.…”
Section: Introductionmentioning
confidence: 99%
“…Barker et al reported binding energies between GO flakes and perfluorinated molecules calculated using density functional theory (DFT) and suggested Van der Waals interactions dominate adsorption. 41 Li et al used first-principles computations of iron on GO flakes to calculate binding strengths as well. 42 Surface complexation modelling has shown some metals adsorb by interacting with carboxyl groups located on the GO flakes.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39] Bulk techniques, namely FTIR, Raman, UV-vis, and xray photoelectron spectroscopy (XPS), have identified varied adsorbed metal-GO binding, ranging from likely electrostatics 23,25 to specific binding with sulfur-and oxygen-based groups, 25,32,40 although the exact binding mechanisms remain unknown. Computational efforts have supported these findings, [41][42] mainly with surface complexation models. 29,[31][32] However, a large gap between computational and experimental agreement still exists.…”
Section: Introductionmentioning
confidence: 92%
“…The wavevector arguments reflect a Fourier transform in (r − r ) of, for example, r|χ λ (ω)|r . The Hubbard approximation for the HEG response, equations (51) and (52), makes it possible to provide an analytical evaluation of the coupling-constant integral. The result is a formal, Hubbard-based specification of the HEG XC energy [25]:…”
Section: Response In the Electron Gasmentioning
confidence: 99%
“…The vdW-DF versions and variants can, for example, be subjected to a formal couplingconstant analysis [14,15,[48][49][50][51] to isolate kinetic-energy, kinetic-correlation-energy, and electron-electron interaction binding contributions. This analysis provides a refined mapping [14,52] of where, for example, the vdW interactions between molecules and at surfaces originate in space [10,[53][54][55][56][57][58][59]. The coupling-constant scaling analysis can also be used to discuss the choice of Fock-exchange mixing in vdW-DF-based hybrids [13,15].…”
Section: Introductionmentioning
confidence: 99%